The nonlinear product of the bessel diamond operator and the bessel klein-gordon operator related to the bessel biharmonic equation - Suntonsinsoungvon E. (2017)
In this article, we study the solution of the equation where {lozenge, open} k B (□ B +m 2 ) k is the product of the Bessel diamond operator and the Bessel Klein-Gordon operator, u is an unknown generalized function, f is a generalized function, m is a positive real number and k is a nonnegative integer. It found that the existence of the solution u(x) of such n equation depends on the condition of f and {increment} k B -1 {lozenge, open} k B (□ B +m 2 ) k u(x). Moreover such a solution u(x) related to the Bessel biharmonic equation depends on the conditions of p, q and k.